Fine structure of heterogeneous vector field and its space averaged polarization characteristics - Brandel, R.; Mokhun, A.; Mokhun, I.; Viktorovskaya, Ju. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Interrelation between the fine structure of the vector field and its averaged polarization characteristics is considered. It is shown that space averaged Stokes parameters are defined by dispersion of the phase difference (or dispersion of the polarization azimuth) at its saddle points. At the same time the dispersion of the phase difference is directly related to averaged space between the nearest adjacent component vortices of the same sign, which are associated with the different orthogonal linearly polarized components. The dependence between the dimensions of areas where considerable polarization changes occur and averaged space between the nearest adjacent component vortices of the same sign is obtained. The results of computer simulation and the experimental investigation are presented.
Optica Applicata, Vol. 36, 2006, nr 1, s. 79-95
Keywords: optyka; vortex; polarization; polarization singularities; coherence matrix; Stokes parameters; phase dispersion; s-contour; C-point; phase difference; integral depolarization